2016
DOI: 10.1088/1361-6528/28/2/025401
|View full text |Cite
|
Sign up to set email alerts
|

Development of SnS2/RGO nanosheet composite for cost-effective aqueous hybrid supercapacitors

Abstract: The development of low cost supercapacitor cells with unique capacitive properties is essential for many domestic and industrial purposes. Here we report the first ever application of SnS-reduced graphene oxide (SnS/RGO) layered nanocomposite as a superior electrode material for symmetric aqueous hybrid supercapacitors. We synthesized SnS/RGO nanocomposite comprised of nanosheets of SnS and graphene oxide via a one-pot hydrothermal approach. in situ as-synthesized SnS/RGO is devised for the first time to give … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 50 publications
3
54
0
Order By: Relevance
“…Figure A, exhibits the typical CV curves of the prepared SnS 2 and SnS 2 /MoS 2 composites at the scan rate of 10mvs ‐1 with the potential window from 0.1V to 0.6V. It can obviously find typical redox peaks in each CV curves from 0.1 V to 0.6 V, which indicated a typical pseudocapacitance behavior that can be ascribed to the insertion of K + ions in the interlayer of SnS 2 and MoS 2 and reversible redox reactions occurring in SnS 2 and MoS 2 , which demonstrated that the capacitance of supercapacitor mainly originate from the faradaic redox reaction. Besides that, due to the different mole ratios of MoS 2 in the prepared composites that the redox peaks of the CV are not at the same position, which effectively indicates that MoS 2 plays an important role in the electrochemical reaction process and makes a great contribution to the capacity improvement.…”
Section: Resultsmentioning
confidence: 90%
“…Figure A, exhibits the typical CV curves of the prepared SnS 2 and SnS 2 /MoS 2 composites at the scan rate of 10mvs ‐1 with the potential window from 0.1V to 0.6V. It can obviously find typical redox peaks in each CV curves from 0.1 V to 0.6 V, which indicated a typical pseudocapacitance behavior that can be ascribed to the insertion of K + ions in the interlayer of SnS 2 and MoS 2 and reversible redox reactions occurring in SnS 2 and MoS 2 , which demonstrated that the capacitance of supercapacitor mainly originate from the faradaic redox reaction. Besides that, due to the different mole ratios of MoS 2 in the prepared composites that the redox peaks of the CV are not at the same position, which effectively indicates that MoS 2 plays an important role in the electrochemical reaction process and makes a great contribution to the capacity improvement.…”
Section: Resultsmentioning
confidence: 90%
“…The emerging properties (e.g., ultrafast charge transfer between van der Waals-coupled layers and tunable optoelectronic properties) [180] and new physical features (e.g., superlattice Dirac points [181] and Hofstadter butterfly in magnetic field [182] ) of 2D hetero-nanosheets are originates from interlayer interactions between different nanosheets. [66,67,103,104,[184][185][186][187] Park and co-workers fabricated RGO/MoS 2 hybrid films via vacuum filtration of a mixture of GO and MoS 2 and subsequent heat-treatment. [183] Some of the 2D nanomaterials are redox active, but charge transfer is too slow to achieve the pseudocapacitance at the specific rate.…”
Section: D Hetero-nanosheetsmentioning
confidence: 99%
“…Transition metal sulfides (MoS 2 and SnS 2 ) with layered structure and large interplanar distance have been applied in energy storage devices in recent years [67][68][69][70]. However, the poor inherent electronic conductivity causes serious polarization and low electrode utilization efficiency.…”
Section: Transition Metal Chalcogenides and Nitridesmentioning
confidence: 99%
“…For example, the layered SnS 2 has a large interlayer spacing of 0.59 nm in favor of the insertion/extraction of Na + . In 2016, Chauhan et al [68] synthesized , respectively. Due to superior electronic conductivity and high pseudocapacitance, the transition metal nitrides are considered as promising electrodes, especially, the VN and TiN [74][75][76].…”
Section: Transition Metal Chalcogenides and Nitridesmentioning
confidence: 99%
See 1 more Smart Citation